The Effect of Maternity Care Health Education Through Leaflet Media on The Level of Knowledge of Pregnant Women - Baity, Feny Nur; Rahayuningsih, Faizah Betty (Jurnal EduHealth, 2023)
Introduction: The Maternal Mortality Rate (MMR) serves as an indicator of the dangers encountered by mothers throughout pregnancy and childbirth, factors of which encompass maternal nutritional well-being, socioeconomic circumstances, pre-pregnancy health status, occurrences of complications during pregnancy and delivery, as well as the accessibility and utilization of healthcare facilities, including health services. Health education, on the other hand, is a purposefully organized procedure designed to offer individuals opportunities for ongoing learning, fostering heightened awareness, and enhancing their proficiency, capabilities, and skills to promote their overall health. Objective: Knowing the influence of health education about childbirth care through leaflet media on the level of knowledge of pregnant women Method: This type of research is quantitative research with a pre-experimental design method with the design used is one group pretest posttest. In this study, the study sample was 30 pregnant women who were divided into 2 intervention groups: Pre Test and Post test. The media used in providing education use pamphlets. Results: analysis results in the Pre Test group with a Mean of 1.33 ± 0.479 and the Post test group with a Mean of 1.70 ± 0.466. The results of the analysis showed a P-Value value of 0.004 (< 0.05). Conclusion: Providing education using leaflets can be an alternative in educational strategies that are more effective in increasing knowledge of maternity care in pregnant women